Association Rule Analysis for Validating Interrelationships of Combined Medication of Compound Kushen Injection in Treating Colon Carcinoma: A Hospital Information System-Based Real-World Study. (30th August 2018) - Yang, Huisheng; Xie, Yanming; Ni, Jisheng; Liu, Yue; Song, Rui; Chen, Cen; Zhuang, Yan; Zhang, Yin
Abstract : Background . Real world evidence is important for informing healthcare practice and developing medical products and has gained broad interest in healthcare. Compound Kushen Injection (CKI) has been widely applied into treatment of colon carcinoma (CC) in China. Postapproval drug assessment related retrospective studies using electrical medical record (EMR) collected from hospital information system (HIS) is one of the most important categories of real-world study (RWS). Based on HIS EMR, interrelationships of combined medication of CKI in treating CC can be validated in real world settings. Methods . This study was conducted based on a large-scale integrated database of EMR derived from HIS. EMR of 3328 patients initially diagnosed with CC among 49, 597 patients treated with CKI were included in the study. Descriptive statistical analyses and apriori algorithm based association rule analyses were performed, respectively, to validate frequency distribution and interrelationships of combined medication of CKI in treating CC. Results . The pharmacological mechanisms of TCMs that have been commonly used in conjunction with CKI include heat-clearing and detoxifying, qi-reinforcing, blood circulation-promoting and stasis-removing, blood-stanching, and qi-regulating. For modern medicines, antibiotics, antineoplastic chemotherapeutic drugs, immunomodulator, 5-HT receptor antagonist drugs, and corticosteroids are most often combined with CKI. The association rules of medication combinations of CKI in treating CC in real world manifest certain laws for both TCMs and modern medicines. They are generally in line with CC treatment guidelines. Conclusions . It is a common practice for CKI to be integrated with both modern medicines and TCMs when treating CC in China. The associations of medication combinations of CKI in treating CC manifest certain laws for both TCMs and modern medicines. The RWS for validating interrelationships of combined medication may provide evidence for rational use of CKI. Further explorations are needed to verify and expand the conclusions.